Legal Analysis of PT Pertamina Corruption Case and Its Impact on SOE Governance - Hilman Nur; Hadi Aulia, Salsabila; Camilliya Fakhriyah Garnita; Fina Asriani; Muhamad Fahri Mawardi (Eastasouth Institute, 2025)
The major corruption case involving PT Pertamina Patra Niaga reflects a serious failure in the implementation of State-Owned Enterprises (SOEs) governance principles. Practices such as fuel adulteration, domestic crude oil exports, and opaque imports through brokers indicate weak internal and external oversight systems. This study aims to analyze the legal impact of the case on the implementation of SOE governance principles. The research method employed is normative legal research with a statutory approach. The findings reveal that although regulations on corruption eradication in SOEs exist, their implementation remains weak. Recommendations include strengthening internal oversight systems, implementing technology in financial monitoring, and enhancing collaboration between SOEs and law enforcement agencies.